Ethical Leadership and Knowledge Hiding: A Moderated Mediation Model of Psychological Safety and Mastery Climate - Men, Chenghao; Fong, Patrick S. W.; Huo, Weiwei; Zhong, Jing; Jia, Ruiqian; Luo, Jinlian (Journal of business ethics, 2020)
According to social learning theory, we explored the relation between ethical leadership and knowledge hiding. We developed a moderated mediation model of the psychological safety linking ethical leadership and knowledge hiding. Surveying 436 employees in 78 teams, we found that ethical leadership was negatively related to knowledge hiding, and that this relation was mediated by psychological safety. We further found that the effect of ethical leadership on knowledge hiding was contingent on a mastery climate. Finally, theoretical and practical implications were discussed for leadership and knowledge management.